2020
DOI: 10.1002/jmv.26039
|View full text |Cite|
|
Sign up to set email alerts
|

Obesity predisposes to the risk of higher mortality in young COVID‐19 patients

Abstract: Although emerging data demonstrated mortality of young COVID-19 patients, no data have reported the risk factors of mortality for these young patients, and whether obesity is a risk for young COVID-19 patients remains unknown. We conducted a retrospective study including 13 young patients who died of COVID-19 and 40 matched survivors. Logistic regression was employed to characterize the risk factors of mortality in young obese COVID-19 patients. Most of the young deceased COVID-19 patients were mild cases at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
4
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(139 citation statements)
references
References 24 publications
(26 reference statements)
8
106
4
12
Order By: Relevance
“…This phenomenon is clearly demonstrated in the scientific literature. Patients with obesity and metabolic syndrome are at greater risk of COVID-19 complications, which can be harmful even in young people (16). In this setting, various mechanisms have been suggested to increase the risk from viral infections, including reduced natural killer cell number and activity, impaired antigen-stimulation responses and low-grade chronic inflammation (17).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is clearly demonstrated in the scientific literature. Patients with obesity and metabolic syndrome are at greater risk of COVID-19 complications, which can be harmful even in young people (16). In this setting, various mechanisms have been suggested to increase the risk from viral infections, including reduced natural killer cell number and activity, impaired antigen-stimulation responses and low-grade chronic inflammation (17).…”
Section: Discussionmentioning
confidence: 99%
“…In a USA study that had children and adolescents hospitalized with COVID-19 obesity was significantly associated with disease severity [33]. A retrospective case-control study of young Chinese patients with COVID-19 showed that obesity was the most important critical factor contributing to their death [34].…”
Section: Epidemiological Datamentioning
confidence: 99%
“…El IMC de los casos mortales por COVID-19 se reportó con valores cuantitativos en medias o medianas, o como variables categóricas en porcentajes. En general, el punto de corte para obesidad fue de un IMC ≥ 30 kg/m 2 con excepción de un estudio de China [26] que utilizó un valor de IMC ≥ 28 kg/m 2 . El porcentaje de obesidad (IMC ≥ 30 kg/m 2 ) se reportó en siete estudios [27][28][29][30][31][32] y los valores se encontraron entre el 10,5 % y el 33,3 %.…”
Section: íNdice De Masa Corporal (Imc) Y Obesidad En Covid-19unclassified
“…El efecto de la obesidad en la mortalidad por COVID-19 se reportó en 10 estudios [26][27][28][29][30][31][32][33][34][35] (Tabla 3). Dos estudios [28,33] presentaron HR para reportar a la obesidad como factor de riesgo para mortalidad comparados con personas no obesas (IMC < 30 Kg/m 2 ) y otros dos estudios [29,31] presentaron medidas para obesidad grados II y III.…”
Section: Efecto De La Obesidad En Mortalidad Por Covid-19unclassified